2016
DOI: 10.1037/dev0000066
|View full text |Cite
|
Sign up to set email alerts
|

Peer effects on Head Start children’s preschool competency.

Abstract: The goals of the present study were to investigate whether young children attending Head Start (N=292; Mage=4.3 years) selected peers based on their preschool competency and whether children’s levels of preschool competency were influenced by their peers’ levels of preschool competency. Children’s peer interaction partners were intensively observed several times a week over one academic year. Social network analyses revealed that children selected peer interaction partners with similar levels of preschool comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 81 publications
1
43
0
Order By: Relevance
“…Respective network research has recently advanced our understanding of peer effects in academic achievement by providing evidence for peer influence among children and adolescents even when the dynamics of social networks were taken into account (Shin and Ryan 2014;DeLay et al 2016a;Rambaran et al 2016). Importantly, most of these network studies also found evidence for homophily, the process that earlier research has largely ignored.…”
Section: This Leads To the Following Hypothesismentioning
confidence: 98%
See 1 more Smart Citation
“…Respective network research has recently advanced our understanding of peer effects in academic achievement by providing evidence for peer influence among children and adolescents even when the dynamics of social networks were taken into account (Shin and Ryan 2014;DeLay et al 2016a;Rambaran et al 2016). Importantly, most of these network studies also found evidence for homophily, the process that earlier research has largely ignored.…”
Section: This Leads To the Following Hypothesismentioning
confidence: 98%
“…Importantly, most of these network studies also found evidence for homophily, the process that earlier research has largely ignored. For instance, studies in the U.S. found that already preschool children prefer to interact with peers with similar levels of competences (DeLay et al 2016a). Similar results emerged among U.S. elementary students (Shin and Ryan 2014), middle school students (DeLay et al 2016b), and high school students (Flashman 2012a;Rambaran et al 2016).…”
Section: This Leads To the Following Hypothesismentioning
confidence: 99%
“…We also replicate and extend previous studies in several ways. Whereas many other studies have used smaller classroom samples to examine peer influence (e.g., Delay, Hanish, Martin, & Fabes, 2016;Justice et al, 2011), we surveyed over 4,200 children about their peer relationships. This replication, which to our knowledge is the largest to examine peer influence on young children, improves on the generalizability and stability of prior findings.…”
Section: A Social Network Analysis Of Elementary School Classroomsmentioning
confidence: 99%
“…Results from these studies using observations are consistent with this study and others using self-reported data. Delay et al (2016), for instance, observed preschool children's peer interaction partners several times a week over one year and found that children's preschool competency was influenced by their peers' levels of competency.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…As we have mentioned earlier, several studies have lent support to the homophily hypothesis, according to which children choose playmates among those who are more similar to themselves, namely in terms of PA levels (e.g., Espelage et al., ; Snyder et al., ). A recent study has shown that, already in preschool, children might be sensitive to behavioral cues, which allow them to select peers based on similarity (see DeLay, Hanish, Martin, & Fabes, ). Consistent with this, it is important that future research addresses issues of selective play, considering that aspects such as similar aggressive behavior or gender may be better ways of studying peer composition (see Fabes et al., ).…”
Section: Discussionmentioning
confidence: 99%